(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2013)
Biometric security system is based on a binary classification problem: reject or accept identity claim. The performance and robustness of biometric security systems can be improved by combining two or more different modalities (speech, face, fingerprint, etc.). In literature, one of the issues is to improve the performance of multimodal biometric system. In this paper, we investigated the performance of multimodal biometric system using different SVM kernel functions and its parameters. Our experiment on XM2VTS dataset shows systems have been developed based on different biometrics characteristics (fingerprint, face, speech, iris etc.) which help to distinguish individuals from each other. Each biometric has its own advantages and drawbacks due to its discriminative power, complexity, robustness involved. Research in last few years has shown that no single modal biometric system can achieve 100% authentication accuracy. This problem can be alleviated by combining two or more biometric modalities [1], also known as the field of multimodal biometric authentication. A user verification scenario involving two modalities (Face and Speech) [2] is figured out in Fig. 1. that the performance of multimodal biometric system is improved with the proper choice of kernel function and its parameters.